2004
DOI: 10.4049/jimmunol.173.8.5046
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Hedgehog Regulates Early Human Thymocyte Differentiation by Counteracting the IL-7-Induced Development of CD34+ Precursor Cells

Abstract: The Hedgehog (Hh) family of signaling molecules normally functions in the development of numerous tissues by regulating cellular differentiation and proliferation. Recent results have demonstrated that the different components of the Hh signaling pathway are expressed in the human thymus. In this study, we investigate the potential role of Sonic hedgehog (Shh) in human intrathymic T cell maturation. Results show that the expression of the two components of the Hh receptor, Patched and Smoothened, is mostly res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 53 publications
2
44
0
2
Order By: Relevance
“…6,21,24 Differences in the molecular regulation of thymocyte development between adult and fetus might account for this discrepancy. We therefore investigated the impact of Hh signaling on the production of DP cells in the adult thymus.…”
Section: Hh Pathway Activation Impedes Reconstitution Of the Dp Pool mentioning
confidence: 99%
See 2 more Smart Citations
“…6,21,24 Differences in the molecular regulation of thymocyte development between adult and fetus might account for this discrepancy. We therefore investigated the impact of Hh signaling on the production of DP cells in the adult thymus.…”
Section: Hh Pathway Activation Impedes Reconstitution Of the Dp Pool mentioning
confidence: 99%
“…1,6,[18][19][20][21][22][23] Analysis of mice mutant for Shh, Gli3, and Smo have shown that Hh signaling is necessary for efficient survival, proliferation, and differentiation of thymocytes at the transition from DN1 to DN2, 18,21,22 but the role of Hh signaling at the transition from DN to DP thymocytes is controversial. Different experimental approaches have produced conflicting results that have led to 3 different interpretations: that Hh is a negative regulator of the pre-TCR signal and differentiation to DP 6,21,24 ; that Shh is a positive regulator of the DN to DP transition 18 ; or that Hh signaling does not influence thymocyte differentiation after the DN2 stage. 22 In vitro studies first demonstrated that Hh signaling influences thymocyte development 6,24 and suggested that Hh signaling was a negative regulator of differentiation to DP cell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These signaling proteins are required for efficient maturation and differentiation of the earliest double negative (DN) populations (3,4,6,7,10,12). Shh also influences TCR repertoire selection, most likely by modulating TCR signal strength (11,29).…”
Section: The Gli3 Transcription Factor Expressed In the Thymusmentioning
confidence: 99%
“…Hedgehog (Hh) 3 proteins secreted by the thymus stroma and the CD4 ϩ CD8 ϩ double positive (DP) thymocytes have important regulatory functions in both mouse thymus (3)(4)(5)(6)(7)(8)(9)(10)(11) and human thymus (12,13). The Hh family of secreted signaling proteins is essential for embryonic development and homeostasis of adult renewable tissues (14 -17), and inappropriate Hh pathway activation is involved in many cancers (18,19).…”
Section: The Gli3 Transcription Factor Expressed In the Thymusmentioning
confidence: 99%